Status of 3C-SiC Growth and Device Technology - Wellmann, Peter; Schöler, Michael; Schuh, Philipp; Jennings, Mike; Li, Fan; Nipoti, Roberta; Severino, Andrea; Anzalone, Ruggero; Roccaforte, Fabrizio; Zimbone, Massimo; Via, Francesco La (wiley, 2021)
Since the early days of research in the field of the wide band gap semiconductor silicon carbide (SiC), the cubic polytype has been favorable because it exhibits the highest electron mobility. The electronic band gap and electric breakdown are slightly smaller than the hexagonal 4H-SiC. Therefore, the ideal operation range of power electronic devices based on 3C-SiC lies in the mid-voltage range of 400-600 V as it is used in the large application field of electric automotive applications. The current review presents a state-of-the-art overview over the complete processing change from materials growth to device processing.
CRIS-Team Scopus Importer:2024-12-16
Keywords: 3C-SiC bulk growth; 3C-SiC device processing; 3C-SiC MOSFET; 3C-SiC thin films; cubic silicon carbide